External validation of the United Kingdom‐primary biliary cholangitis risk scores of patients with primary biliary cholangitis treated with ursodeoxycholic acid. Issue 6 (24th April 2018) - Cheung, Angela C.; Gulamhusein, Aliya F.; Juran, Brian D.; Schlicht, Erik M.; McCauley, Bryan M.; de Andrade, Mariza; Atkinson, Elizabeth J.; Lazaridis, Konstantinos N.
Abstract : The United Kingdom‐Primary Biliary Cholangitis (UK‐PBC) risk scores are a set of prognostic models that estimate the risk of end‐stage liver disease in patients with PBC at 5‐, 10‐ and 15‐year intervals. They have not been externally validated outside the United Kingdom. In this retrospective, external validation study, data were abstracted from outpatient charts and discrimination and calibration of the UK‐PBC risk scores were assessed. A total of 464 patients with PBC treated with ursodeoxycholic acid were included. The median diagnosis age was 52.4 years, and 88% were female patients. The cumulative incidence of events was 6%, 9%, and 15% at 5, 10, and 15 years, respectively. Concordance (c‐statistic) was 0.88, 0.85, and 0.84 using the 5‐, 10‐ and 15‐year risk scores, respectively, which was slightly lower than values observed in the United Kingdom validation cohort. Using the 5‐year risk score, more events were observed than predicted (25 versus 16.8; P = 0.046); using the 10‐year risk score, there was no difference between the observed and predicted number of events (35 versus 44.9; P = 0.14); conversely, using the 15‐year risk score, fewer events were observed than predicted (46 versus 67.5; P = 0.009). Limiting evaluation by the 15‐year UK‐PBC risk score to those with >10 years of follow‐up demonstrated no difference between observed and predicted events. Using the 5‐year risk score, patients within the highest quartile had statistically significant worse event‐free survival compared to the rest of the cohort: 82% versus 98% at 5 years, 73% versus 97% at 10 years, and 58% versus 93% at 15 years. Conclusion: In patients assessed at a North American tertiary medical center, the UK‐PBC risk score had excellent discrimination and was reasonably calibrated both in the short and long term. ( Hepatology Communications 2018;2:676‐682)